An Outbreak Investigation of Jaundice Cases in Vadodara District - Alpesh S Patel; Pankaj P Taviad; Raman D Damor (Medsci Publications, 2018)
Background: Water, sanitation, and hygiene related infectious dis- eases are common in India. The Hepatitis E virus (HEV) virus is transmitted by the fecal-oral route. Transmission of HEV through contaminated water is the major concern for public health. Materials and method: Present outbreak investigation was carried out by rapid response team of medical college Vadodara. Outbreak investigation was carried out to find out probable source of infec- tion, etiological agent, mode of transmission and to provide tech- nical support for prevention and control of epidemic. Consump- tion of contaminated water was suspected as primary source of in- fection for formation of hypothesis. Blood samples of clinically suspected cases and water samples from various sites were col- lected for laboratory confirmed diagnosis of disease under investi- gation. Results: Total 42 jaundice cases were reported. Attack rate was higher in male (14.47 per 1000 population) compare to female (8.16 per 1000 population). Diagnosis of viral hepatitis E was confirmed by blood investigations Conclusion: Mixing of contaminated water with piped water dis- tribution system was the primary source of infection and disease was spread through consumption of contaminated water  was  mode of transmission. Various measures for prevention and con- trol of hepatitis E Outbreak were suggested.